Effect of Monoacylglycerol Lipase Inhibition on Intestinal Permeability of Rats With Severe Acute Pancreatitis - Wang, Jing; Xu, Hongwei; Chen, Tianjie; Xu, Changqin; Zhang, Xiaohua; Zhao, Shulei (Frontiers in Pharmacology, 2022)
Background: Endocannabinoid 2-arachidonoylglycerol (2-AG) is an anti-nociceptive lipid that is inactivated through cellular uptake and subsequent catabolism by monoacylglycerol lipase (MAGL). In this study, we investigated the effects of MAGL inhibition on intestinal permeability and explored the possible mechanism. Methods: A rat model of severe acute pancreatitis (SAP) was established. Rats were divided into three groups according to treatment. We analyzed intestinal permeability to fluorescein isothiocyanate-dextran and the levels of inflammatory factors interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) and 2-AG. Hematoxylin and eosin staining was used to assess histological tissue changes. In vivo intestinal permeability was evaluated by transmission electron microscopy. We obtained ileum tissues, extracted total RNA, and applied RNA-sequencing. Sequencing data were analyzed by bioinformatics. Results: Inflammatory factor levels were higher, while 2-AG levels were lower in the SAP group compared with the control group. Administration of JZL184 to rats with SAP increased the levels of 2-AG and lowered the levels of IL-6 and TNF-α. Notably, intestinal permeability was improved by JZL184 as demonstrated by fluorescein isothiocyanate-dextran measurement, hematoxylin and eosin staining, and transmission electron microscopy. RNA-sequencing showed significant transcriptional differences in SAP and JZL184 groups compared with the control group. KEGG analysis showed that the up- or downregulated genes in multiple comparison groups were enriched in two pathways, focal adhesion and PI3K-Akt signaling pathways. Differential alternative splicing (AS) genes, such as Myo9b, Lsp1, and Git2, have major functions in intestinal diseases. A total of 132 RNA-binding proteins (RBPs) were screened by crossing the identified abnormally expressed genes with the reported RBP genes. Among them, Hnrnpdl coexpressed the most AS events as the main RBP. Conclusion: MAGL inhibition improved intestinal mucosal barrier injury in SAP rats and induced a large number of differentially expressed genes and alternative splicing events. Hnrnpdl might play an important role in improving intestinal mucosal barrier injury by affecting alternative splicing events.